Effect of Performance Measurement System, Reward System, Implementation of Total Quality Management and Organizational Commitment on Managerial Performance in Pt. Socfindo Medan - Siti Hamdayani Purba (TRIGIN PUBLISHER, 2020)
This study aims to determine the effect of performance measurement system, reward system, application of total quality management, and organization commitment on managerial performance either partially or simultaneously at PT. Socfindo Medan. This type of research is a causal associative. This research was conducted at PT. Socfindo Medan with research time for one month and using likert scale. The population of this research is PT. Socfindo Medan as many as 61 respondents and samples taken by using purposive sampling method so that the number of samples as much as 41 respondents. The data source of this research is primary data obtained through observation and spreading of questionnaire to staff. Data analysis techniques use data quality tests, descriptive statistical analysis, classical assumption tests and hypothesis tests. The results showed that in partial performance measurement system, application of total quality management and organization commitment variable had positive and significant influence on managerial performance, while reward system variable has positive and not significantly influenced on managerial performance. Simultaneously performace measurement system, reward system, application of total quality management, and organization commitment variables have significantly influenced on managerial performance at PT. Socfindo Medan.